Pengaruh Beberapa Konsentrasi Ekstrak Umbi Teki (Cyperus rotundus) Terhadap Perkecambahan Biji Gulma Susupan Gunung (Neptunia oleracea) - Minarahmi, Putri; Aphrodyanti, Lyswiana (JURNAL PROTEKSI TANAMAN TROPIKA, 2025)
This study aims to determine the effect of Cyperus rotundus tuber extract on mortality and final germination of seeds of the weed Neptunia oleracea. The research was carried out using a Completely Randomized Design (CRD) consisting of five concentration treatments, namely 0% (control), 15%, 30%, 45% and 60%, each of which was repeated four times. Parameters observed included mortality rate, final germination and germination length. The results of the study showed that administration of nut tuber extract (C. rotundus) did not have a significant effect on mortality or final germination of seeds of the weed N. oleracea. However, there is a tendency that the higher the concentration of the extract given, the greater the percentage of inhibition that occurs. This shows the potential for allelopathic effects which need to be explored further through research with different concentrations and application methods.